THE DIFFICULTIES AND STRATEGIES OF EFL STUDENTS IN IMPROVING THEIR ENGLISH SKILLS - Tukan, Fransiska M. Ena (Sanata Dharma University Yogyakarta, 2024)
This paper aims to explain the difficulties of EFL students in learning English, the difficulties in writing skills, and the strategies used to improve their writing skills. The participants were 20 students of SMPK. St. Isidorus, Lewolema sub-district, East Flores, Nusa Tenggara Timur. A qualitative method was employed in this research using the interview as a data collection technique. The findings showed that the difficulties of EFL Students in learning English where they cannot (1) translate the English words, (2) read an English text, (3) write an English sentence, (4) pronounce, and (5) memorize the English sentence. Students have difficulties in writing such as lack of vocabulary, cannot write the word in English correctly, and translate the sentence in English. The strategies chosen by the students to improve their writing include learning how to translate the word, memorize the vocabulary, and learn to write the correct English sentence.